Influence of Social Media Marketing and Brand Ambassadors on Dabe Beaute Purchase Intention with Brand Awareness as an Intervening Variable in Jabodetabek - Novrian; Sufrin Hannan; Agus Setyo Pranowo (International Journal of Economics Accounting and Management, 2026)
This research aims to analyze the influence of Social Media Marketing and Brand Ambassadors on consumer purchase intention in Dabe Beaute products, both directly and indirectly thru Brand Awareness. This research uses a quantitative approach with a survey method. Data was collected from 196 respondents who were potential Dabe Beaute customers in the Jabodetabek area, using purposive sampling techniques. Data analysis was conducted using the Structural Equation Modeling based on Partial Least Squares (SEM-PLS) method. The research results indicate that Social Media Marketing and Brand Ambassadors have a positive and significant influence on Purchase Intention. Additionally, Social Media Marketing and Brand Ambassadors are also proven to have a positive and significant influence on Brand Awareness. However, Brand Awareness does not significantly influence Purchase Intention. The results of the mediation effect test show that Brand Awareness is unable to mediate the influence of Social Media Marketing or Brand Ambassadors on Purchase Intention. This finding confirms that the influence of Social Media Marketing and Brand Ambassadors on Purchase Intention occurs more dominantly directly. Companies need to design digital marketing strategies that emphasize engaging content and the selection of relevant Brand Ambassadors to increase consumer purchasing intention.